2019
DOI: 10.1002/joc.6306
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in mid–high‐latitude Eurasian climate during boreal spring in a 1.5 and 2°C warmer world

Abstract: This study examines projected changes in surface air temperature (SAT) and precipitation over mid–high latitudes of Eurasia during boreal spring in a 1.5/2°C warmer world (relative to pre‐industrial level) using historical, RCP4.5 and RCP8.5 simulations from 16 climate models of the Coupled Model Intercomparison Project Phase 5. Results show that spatial patterns of spring SAT and precipitation changes over Eurasia in the 1.5/2°C warmer world relative to the current climate (1979–2005) are similar between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Studies applied to other regions of the globe have identified patterns similar to those in this study. For example, projections indicate that Europe will be 1°C warmer than the global average for a global warming of 2°C (Sanderson et al ., 2017) and the springs in China will be 0.5°C warmer than the global average, both for 1.5 and 2°C (Chen et al ., 2020a). Furthermore, Shi et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies applied to other regions of the globe have identified patterns similar to those in this study. For example, projections indicate that Europe will be 1°C warmer than the global average for a global warming of 2°C (Sanderson et al ., 2017) and the springs in China will be 0.5°C warmer than the global average, both for 1.5 and 2°C (Chen et al ., 2020a). Furthermore, Shi et al .…”
Section: Resultsmentioning
confidence: 99%
“…For example, projections indicate that Europe will be 1 C warmer than the global average for a global warming of 2 C (Sanderson et al, 2017) and the springs in China will be 0.5 C warmer than the global average, both for 1.5 and 2 C (Chen et al, 2020a). Furthermore, Shi et al (2018) pointed out that northern China will experience faster and more intense warming compared to southern China.…”
Section: Patterns Of Temperature and Precipitation Change In South Am...mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these have been accompanied by large numbers of papers using climate models that postulate a range of scenarios to project future temperatures to the end of the 21st century (e.g., Jacob et al ., 2014; Kumar et al ., 2014; Gross et al ., 2019). Also frequent are papers estimating the consequences of temperature increases of certain values for other climatological characteristics or phenomena (e.g., Belda et al ., 2016; Naumann et al ., 2018; Xu et al ., 2019; Chen et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Figure S1 shows differences in the central years and the global warming target periods for each RCP and GCM. The results indicate large spreads in the central year of 1.5 and 2.0 • C warming across all 5 GCMs under RCP4.5 relative to RCP8.5 (Zhang et al, 2019;Chen et al, 2020). The central year for the 1.5 • C (2.0 • C) warming condition derived from the MME of the 5 GCMs is 2028 (2051) under RCP4.…”
Section: No Gcm Resolution Institute Nationmentioning
confidence: 88%